Responsività - Ferraris, Maurizio (Bollettino Filosofico, 2019)
In my contribution, I propose to define the subjective pole of otherness, namely the ability to respond and react to the other (human, animal, or inanimate) that is characteristic of the human being. Instead of being halfway between an animal and the Übermensch, as Nietzsche claimed, or in between an angel and an animal, as Pascal suggested, the human being is halfway between an animal and an automaton. Non-human animals only have the organism, and machines only the mechanism, while humans place themselves at the intersection between mechanism and organism: that is, they have responsiveness. And responsiveness (whose basic form lies in sensitivity and irritability, in terms of red eyes, an itch or a cough, while its most manifest form, philosophically, is reason as the faculty of ends) is where lies the decisive difference between human and automaton. This difference does not consist in some supplement of the spiritual soul, but in the animal nature that characterizes us as organisms. We are human because we are animals and we are more complex souls than non-human animals because we have-in us and especially outside of us-very powerful automata that are called language, culture, and technology. Keywords: Otherness, Animal, Automaton, Mechanism, Organism